PENGARUH INTENSITAS KOMUNIKASI PEER GROUP DAN TERPAAN CELEBRITY ENDORSER DI MEDIA SOSIAL TERHADAP MINAT MENGGUNAKAN ROKOK ELEKTRIK (VAPE) PADA REMAJA - Aldiansyah, Duvit; Pradekso, Tandiyo; Naryoso, Agus (Interaksi Online, 2024)
E-cigarettes (electronic cigarettes) or vape have become a new consumption trend by teenagers, supported by the latest data where the highest number of vape users in Indonesia, around 22 percent, are teenagers aged 15 to 19 years. Studies show that if you have friends who smoke, over time they tend to become people who intend to, experiment, or become regular smokers. Apart from that, the presence of celebrity endorsers who support a brand can also increase purchase intentions. This research is a type of explanatory quantitative research. Social Learning Theory is used to explain the relevance of peer group communication to interest in using. Meanwhile, when exposed to celebrity endorsers, the Source Credibility Model is used as a theoretical basis. A simple linear regression test on the intensity of peer group communication on interest in using electronic cigarettes (vape) shows a significance value of 0.000, which means it is very significant or there is an influence so the hypothesis can be accepted. The significance value of exposure to celebrity endorsers on interest in using electronic cigarettes (vape) is 0.000, which means it is very significant because 0.000 ≤ 0.01 so the hypothesis is accepted where there is an influence.